1976
DOI: 10.1212/wnl.26.4.311
|View full text |Cite
|
Sign up to set email alerts
|

Rapid eye movement sleep alterations in myasthenia gravis

Abstract: The nocturnal sleep patterns of 10 patients with myasthenia gravis and five controls were recorded in the conventional manner for 7 hours on two consecutive nights. One patient was retested 4 weeks after institution of prednisone therapy. All the myasthenics had a significant disturbance in rapid eye movement (REM) sleep cycles. In the patient who was retested after clinically successful prednisone therapy, the REM sleep pattern had become normal. Since acetylcholine is the putative brain stem transmitter subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0
2

Year Published

1978
1978
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 0 publications
2
22
0
2
Order By: Relevance
“…Sleep-disordered breathing is common in MG associated with peripheral respiratory muscle weakness, particularly diaphragmatic weakness. In common with other conditions, sleep-disordered breathing and nocturnal desaturation are most pronounced during REM sleep [16,18] and the majority of respiratory events are central. Older patients with a higher BMI, lower TLC and abnormal daytime arterial blood gases are most vulnerable [16].…”
Section: Myasthenia Gravismentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep-disordered breathing is common in MG associated with peripheral respiratory muscle weakness, particularly diaphragmatic weakness. In common with other conditions, sleep-disordered breathing and nocturnal desaturation are most pronounced during REM sleep [16,18] and the majority of respiratory events are central. Older patients with a higher BMI, lower TLC and abnormal daytime arterial blood gases are most vulnerable [16].…”
Section: Myasthenia Gravismentioning
confidence: 99%
“…Older patients with a higher BMI, lower TLC and abnormal daytime arterial blood gases are most vulnerable [16]. Sleep-disordered breathing and nocturnal desaturation may improve following treatment with thymectomy [17] or prednisolone [18].…”
Section: Myasthenia Gravismentioning
confidence: 99%
See 1 more Smart Citation
“…Two groups have tried to use EEG sleep studies of the amount and timing of REM sleep to demonstrate central cholinergic abnormalities, but their results have apparently been discrepant. The first, by Papazian (1976), reported decreased and disturbed REM sleep. The second, by Mennuni et al (1983), found decreased REM latency.…”
Section: Myasthenia Gravismentioning
confidence: 99%
“…For instance, old studies reported increased incidence of epilepsy and electrophysiological changes in patients with MG 3,4 . Sleep disorders and memory impairment have also been described in MG, as the cholinergic system plays a major role in these functions 5,6 . However, the inappropriate methods of these previous studies precluded the establishment of any causal relationship between these findings and disruption of cholinergic neurotransmission 2 .…”
mentioning
confidence: 99%